TESTING OF WORK-FAMILY ENRICHMENT THROUGH WORK ENGAGEMENT - Hidayah, Siti Nurul; palupiningdyah, palupiningdyah (Management Analysis Journal, 2019)
This study aims to determine the effect of job crafting and leader-member exchange on work-family enrichment through work engagement on married women  employees in the finishing department of PT Sandang Asia Maju Abadi. The type and design of the research used in this study is quantitative research. Sampling in this study used a probability sampling and obtained the sample size that must be used is 127 employees. Methods of data collection using a questionnaire with a Likert scale 1-5. The analytical method used is the test instrument (validity and reliability), hypotheses testing and path analysis test with SPSS 23. The results of the study show that all hypotheses are accepted. Therefore could be known that job crafting has a positive effect on work engagement. Leader-member exchanges have a positive effect on work engagement. Job crafting has a positive effect on work-family enrichment. Leader-member exchanges have a positive effect on work-family enrichment. Work engagement has a positive effect on work-family enrichment. The path analysis test results also show that job crafting has a positive effect on work-family enrichment and leader-member exchange that has a positive effect on work-family enrichment through work engagement.